1998
DOI: 10.4269/ajtmh.1998.59.431
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgM antibody response to the galactose-inhibitable adherence lectin of Entameoba histolytica.

Abstract: Abstract. An ELISA for detection of serum IgM antibodies to the galactose-inhibitable adherence lectin of Entamoeba histolytica revealed that 2.8% of uninfected controls, 0.0% of controls infected with other parasites, 13.4% of asymptomatic amebic infections, 55% of colitis patients, and 77% of amebic liver abscess patients from Cairo, Egypt and Durban, South Africa had serum anti-lectin IgM antibodies. Of acute amebic colitis patients with symptoms for less than one week, only 6% possessed serum IgG anti-lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
2
21
1
2
Order By: Relevance
“…Conversely, because the serosurvey detected a sustained antibody response that persisted even after the infection, 33,34 it contributed to the higher prevalence of infection in the present study compared with that in the 1992 survey. The seroprevalence we found in the current study provides an overview of E. histolytica infection in China, but does not provide information on the incidence of amebiasis.…”
Section: Discussioncontrasting
confidence: 40%
“…Conversely, because the serosurvey detected a sustained antibody response that persisted even after the infection, 33,34 it contributed to the higher prevalence of infection in the present study compared with that in the 1992 survey. The seroprevalence we found in the current study provides an overview of E. histolytica infection in China, but does not provide information on the incidence of amebiasis.…”
Section: Discussioncontrasting
confidence: 40%
“…The purified lectin in native and recombinant forms is a highly conserved antigen. In over 95% of samples obtained from hundreds of patients cured of amebic colitis or liver abscess studied worldwide, native lectin protein purified from a single cloned E. histolytica isolate is recognized by serum immunoglobulin G (IgG), IgM, and IgA antibodies (1,3,5,6,21,32). The same has been found from subjects with noninvasive asymptomatic E. histolytica intestinal infection (28,31).…”
mentioning
confidence: 62%
“…Serum IgG antibodies persist for years after E. histolytica infection, whereas the presence of IgM antibodies is shortlived and can be detected during the present or current infection. An ELISA for detection of serum IgM antibodies to amebic adherence lectin was successfully used with patients suffering from acute colitis for less than 1 week, as 45% had detectable antilectin IgM antibodies (1). In another study, it was shown that an assay based on the detection of anti-LC3 (recombinant cysteine-rich portion of the E. histolytica galactose-inhibitable lectin's 170-kDa subunit) antibodies in saliva is a more sensitive and specific test for diagnosis of ALA and acute amebic colitis than detection of serum anti-LC3 IgG antibodies (2).…”
Section: Antibody Detection Testsmentioning
confidence: 99%